2006
DOI: 10.1111/j.1751-3928.2006.tb00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Occurrence and Characteristics of Mn‐ore Bodies in Iron Ore Group of Rocks, North Orissa, India and Its Significance in Resource Evaluation

Abstract: Several meso-scale manganese ore bodies, scattered within Jone's horse-shoe shaped synclinorium, in Bonai-Keonjhar region of north Orissa are well known in the mineral map of India. Different grades of manganese ores are being exploited from this region by various agencies over a few decades. However, deceptive nature of ore bodies and complexity in control of mineralisation greatly confuse the exploration geologists for evaluation of these resources.In a recent study, the authors have classified Mn-ore bodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 3 publications
(3 reference statements)
3
22
0
Order By: Relevance
“…Mineral assemblages of those ore samples are listed in Table 1. The mineralogical data are comparable to those of Mishra et al (2006), who also reported the presence of romanechite in the stratiform and lithiophorite in the stratabound ores.…”
Section: Analytical Proceduressupporting
confidence: 84%
See 4 more Smart Citations
“…Mineral assemblages of those ore samples are listed in Table 1. The mineralogical data are comparable to those of Mishra et al (2006), who also reported the presence of romanechite in the stratiform and lithiophorite in the stratabound ores.…”
Section: Analytical Proceduressupporting
confidence: 84%
“…These extensive iron beds are similar to the Lake Superior‐type BIF (Banerji, 1977). There are a number of manganese orebodies within chert and/or shale as layers and lenses (Banerji, 1977; Mohapatra et al , 1996; Mishra et al , 2006).…”
Section: Geology Of Late Archean Manganese‐iron Belt In East Indiamentioning
confidence: 99%
See 3 more Smart Citations